Effect of management systems on porosity and water retention in Lateritic Reddish-Brown Dystrophic soil - Farias, Gonçalo S.; Cassol, Elemar A.; Mielniczuk, João (Pesquisa Agropecuaria Brasileira, 2014)
The effect of tillage systems on soil-air-water relationships was studied through the determination of some physical properties in a Lateritic Reddish-Brown Dystrophic soil (Paleudult), which received for five years the following treatments: 1) native pasture; 2) rotation clover-wheat/ soybeans in conventional tillage; 3) wheat/soybeans in no-tillage; 4) wheat/soybeans in conventional tillage; 5) wheat/maize in conventional tillage; 6) wheat/soybeans in minimum tillage; 7) wheat/maize in no-tillage. The results did not show marked and lasting effects of tillage systems on the pore size distribution and soil water retention, thus giving indication that physical deterioration of this soil is basically concerned with water erosion.